Effects of histamine and its antagonists on murine T-cells and bone marrow-derived dendritic cells - Hu XF; Zafar MI; Gao F (Dove Medical Press, 2015)
Xiufen Hu,1,* Mohammad Ishraq Zafar,2,* Feng Gao2 1Department of Paediatrics, Tongji Hospital, 2Department of Endocrinology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China *These authors contributed equally to this work Abstract: We determined the effects of histamine and its antagonists on the surface marker expression of dendritic cells (DCs) and the influence of lipopolysaccharide (LPS), histamine, and histamine receptor antagonists on DCs and T-cells. The bone marrow was extracted from the femurs and tibiae of 6- to 8-week-old female Balb/c mice and cultured in medium containing penicillin, streptomycin, L-glutamine, fetal calf serum, or granulocyte macrophage colony-stimulating factor (GM-CSF) alone or with interleukin (IL)-4. The cells received three different doses of LPS and histamine, plus three different doses of descarboethoxyloratadine (DCL). We assayed the supernatant for various cytokines. The spleen cells of DO11.10 mice were examined by flow cytometry, which included labeling and sorting CD4+ T-cells, as well as coculture of DCs and T-cells with ovalbumin (OVA)323–339 peptide. Histamine or histamine plus DCL did not affect the expression of major histocompatibility complex class II, CD11c, CD11b, CD86, and CD80. However, GM-CSF increased the expression of all markers except CD80. Histamine increased interferon-γ production in GM-CSF + IL-4-cultured cells; it also enhanced IL-10 production, but suppressed IL-12 production in LPS-stimulated DCs with no DCL. Cimetidine inhibited IL-10 production and restored IL-12 secretion in LPS-treated DCs. LPS increased IL-10 and decreased IL-12 levels. GM-CSF + IL-4-generated DCs had a stronger stimulatory effect on DO11.10 T-cell proliferation than GM-CSF-generated DCs. Inducible costimulator ligand expression was higher in GM-CSF + IL-4- than in GM-CSF-generated DC groups after 2 days of coculture, but decreased 4 days later. IL-13 production was higher in bone marrow DCs generated with GM-CSF than in those generated with GM-CSF + IL-4. OVA-pulsed DCs and OVA-plus-DCL DCs showed increased IL-12 levels. OVA plus LPS increased both IL-10 and interferon-α. Although histamine or histamine receptor-1 antagonists did not influence DC LPS-driven maturation, they influenced cytokine production. LPS and GM-CSF influenced surface marker expression and cytokine production. Keywords: dendritic cells, Th1, Th2, histamine, histamine receptor antagonist, costimulatory molecule